Growth evolution and formation mechanism of η′-Cu6Sn5 whiskers on η-Cu6Sn5 intermetallics during room-temperature ageing. (15th January 2020) - Zhang, Z.H.; Wei, C.W.; Han, J.J.; Cao, H.J.; Chen, H.T.; Li, M.Y.
Abstract: The phase-transformation-induced damage of Cu6 Sn5 is an emerging reliability issue in the manufacturing of 3D ICs. Although the retarded phase transformation from η -Cu6 Sn5 to η ′-Cu6 Sn5 at room temperature can produce a large expansion in volume, how the transformation stress threatens the joint reliability during usage is poorly understood. In this paper, the evolution characteristics of quenched η -Cu6 Sn5 bumps were observed during ageing at 25 °C for 1–40 d Due to the retarded phase transformation, η ′-Cu6 Sn5 whiskers spontaneously nucleated and grew on the surfaces of η -Cu6 Sn5 bumps. The orientation relationship between the two phases favourable for whisker growth was confirmed, and two necessary conditions for whisker formation were discussed. In addition, the potential harmfulness of whisker growth was analysed. The study will help expose the phase-transformation-induced damage of Cu6 Sn5 during room-temperature ageing and may reduce the failure risk of entire Cu6 Sn5 intermetallic joints in future large-scale applications of 3D ICs. Graphical abstract: Image, graphical abstract